Late INa Blocker GS967 Supresses Polymorphic Ventricular Tachycardia in a Transgenic Rabbit Model of Long QT Type 2. (August 2020) - Hwang, Jungmin; Kim, Tae Yun; Terentyev, Dmitry; Zhong, Mingwang; Kabakov, Anatoli Y.; Bronk, Peter; Arunachalam, Karuppiah; Belardinelli, Luiz; Rajamani, Sridharan; Kunitomo, Yukiko; Pfeiffer, Zachary; Lu, Yichun; et al.
Abstract : Background: Long QT syndrome has been associated with sudden cardiac death likely caused by early afterdepolarizations (EADs) and polymorphic ventricular tachycardias (PVTs). Suppressing the late sodium current (INaL ) may counterbalance the reduced repolarization reserve in long QT syndrome and prevent EADs and PVTs. Methods: We tested the effects of the selective INaL blocker GS967 on PVT induction in a transgenic rabbit model of long QT syndrome type 2 using intact heart optical mapping, cellular electrophysiology and confocal Ca 2+ imaging, and computer modeling. Results: GS967 reduced ventricular fibrillation induction under a rapid pacing protocol (n=7/14 hearts in control versus 1/14 hearts at 100 nmol/L) without altering action potential duration or restitution and dispersion. GS967 suppressed PVT incidences by reducing Ca 2+ -mediated EADs and focal activity during isoproterenol perfusion (at 30 nmol/L, n=7/12 and 100 nmol/L n=8/12 hearts without EADs and PVTs). Confocal Ca 2+ imaging of long QT syndrome type 2 myocytes revealed that GS967 shortened Ca 2+ transient duration via accelerating Na + /Ca 2+ exchanger (INCX )-mediated Ca 2+ efflux from cytosol, thereby reducing EADs. Computer modeling revealed that INaL potentiates EADs in the long QT syndrome type 2 setting through (1) providing additional depolarizing currents during action potential plateau phase, (2) increasing intracellular Na + (Nai ) that decreases the depolarizing INCX thereby suppressing the action potential plateau and delaying the activation of slowly activating delayed rectifier K + channels (IKs ), suggesting important roles of INaL in regulating Nai . Conclusions: Selective INaL blockade by GS967 prevents EADs and abolishes PVT in long QT syndrome type 2 rabbits by counterbalancing the reduced repolarization reserve and normalizing Nai . Abstract : Supplemental Digital Content is available in the text.